Lincoln Cathedral
The inspiration for tierceron vaulting may be largely due to construction of the Chapter House at Lincoln whose central column, with twenty ribs, fans out to meet similar ribs from each of the ten sides. The only previous polygonal chapter house in England was that of Worcester Cathedral. Built in 1120, it also had a central column which supported groined vaults.